Effect of long-term use of Eurycoma Longifolia Jack on the liver - Alfaqeh, Hamoud Hussein Mohammed (2014)
In present years, the use of Eurycoma longifolia Jack (ELJ) has increased dramatically in Southeast Asia especially Malaysia where it is widely used as aphrodisiac and anti-malarial agents. Interestingly, its consumption has become popular in daily life as beverage to enhance energy and stamina especially among males. However, its effect on the safety of vital organs of the body is not studied properly. Hence, the main objective of this study was to determine whether or not long-term use of ELJ has side effects on liver in rats. Three different concentrations of aqueous extract of ELJ were prepared and dissolved in distilled water, a total of thirty two Sprague-Dawley male rats were used and randomly divided into three test groups and control. The three test groups were given different doses (low dose 250 mg/kg bw, medium dose 500 mg /kg bw and high dose 1000 mg/kg bw) of aqueous extract of ELJ, respectively. Control group was given distilled water alone. Doses were given orally and daily for about 5 weeks. After thirty days, animals were sacrificed; whole liver tissues were obtained, fixed in 10 percent formaldehyde solution overnight for histological examination. Histological observations were showed mild to moderate degrees of hemorrhage, hepatocytes degeneration and severe fatty changes in liver tissue of the test groups treated with ELJ with comparable to control. As a conclusion, the long-term daily consumption of ELJ as beverage may cause fatty changes, hemorrhage and hepatocytes degeneration in the liver tissue when taken in large quantity for long time.